(untitled) (Perner’s Contacts, 2012)
This article gives an overview of technologies used in location based services and telematic services, identifies key components of both services (which consist of wireless data and mobile technologies, location and identification technologies, mobile devices and information systems) and analyses their mutual relationship. On the basis of analysis of both services mutual relationship this article affirms convergence of location based services and telematic services and tries to examine means of utilization of location based services in telematic systems.